Surface plasmon resonance based immunosensor for the detection of the cancer biomarker carcinoembryonic antigen - Altintas, Zeynep; Uludag, Yildiz; Gurbuz, Yasar; Tothill, Ibtisam E. (Elsevier Science B.V., Amsterdam., 2011)
An immunoassay in optimised conditions with a highly sensitive surface plasmon resonance (SPR) based biosensor was developed for the detection of the cancer biomarker carcinoembryonic antigen (CEA). Different formats of the immunoassay were initially investigated on the surface of the gold sensor chip. A self- assembled monolayer (SAM) was formed on the gold chip using 11- mercaptoundecanoic acid (MUDA), before the immobilisation of the antibodies was conducted. The assay was then formed in a direct capture and a sandwich assay. In order to increase the sensor signal the CEA antigen was incubated with the detection/capture antibody before it was injected to the sensor chip surface and the results were recorded in real-time using the Biacore 3000 instrument. A detection limit of 3ngml-1 CEA was obtained with a dynamic detection range from 3ngml-1 to 400ngml-1 with correlation coefficients of 1.00 and 0.99 for the sandwich and rabbit anti-mouse (RAM) capture assay. Kinetic data analysis was performed for the standard capture test and subsequently for the developed assays and Rmax showed an increase from 215 RU for the standard capture test to 428 RU for the RAM-capture assay and 734 RU for the sandwich assay, respectively. The developed SPR immunosensor using the sandwich assay format showed high sensitivity and reproducibility for CEA detection which makes it a promising procedure for cancer biomarker analysis
Keywords: Carcinoembryonic antigen; Immunoassay; SPR; Early diagnosis of cancer; Homogeneous assay